A probable case of collapse due to hyoscine patch. Issue 9 (7th September 2021) - Ale, Pramol; Munaf, Asif; Kemp, Timothy
Abstract : This case report highlights the potentially serious side effects of hyoscine and how a seemingly innocuous patch may confound patients and doctors alike. It demonstrates how easy it is to miss an obvious diagnosis when in fact a thorough medical history including an exhaustive drug history can easily point us in the direction of the diagnosis fairly quickly. Finally, hyoscine may cause potentially serious side effects and patients who are taking it, either orally or transdermally, should be made aware of these.